To find \((f \cdot g)(x)\), we need to multiply the two functions \(f(x)\) and \(g(x)\).
Given:
- \(f(x) = x\) (the length of the rectangle)
- \(g(x) = x + 3\) (the width of the rectangle)
The product of the two functions is calculated as follows:
\[ (f \cdot g)(x) = f(x) \cdot g(x) = x \cdot (x + 3) \]
Now, we can simplify the expression:
\[ (f \cdot g)(x) = x \cdot (x + 3) = x^2 + 3x \]
This expression, \(x^2 + 3x\), represents the area \(A\) of the rectangle as a function of \(x\), where \(x\) is the length and \(g(x)\) is the width of the rectangle.
Thus, the interpretation is:
\[ A(x) = x^2 + 3x \text{ square feet} \]
This means that for a rectangle with length \(x\) feet and width \(x + 3\) feet, the area can be expressed as \(x^2 + 3x\) square feet.